PIK3CA mutations are frequent in esophageal squamous cell carcinoma associated with chagasic megaesophagus and are associated with a worse patient outcome - Munari, Fernanda Franco; Cruvinel-Carloni, Adriana; Lacerda, Croider Franco; De Oliveira, Antônio Talvane Torres; Scapulatempo-Neto, Cristovam; Da Silva, Sandra Regina Morini; Crema, Eduardo; Adad, Sheila Jorge; Rodrigues, Maria Aparecida Marchesan [UNESP]; Henry, Maria Aparecida Coelho Arruda [UNESP]; Guimarães, Denise Peixoto; Longatto-Filho, Adhemar; et al. (Springer Nature, 2018)
Background: Chronic diseases such as chagasic megaesophagus (secondary to Chagas' disease) have been suggested as etiological factors for esophageal squamous cell carcinoma; however, the molecular mechanisms involved are poorly understood. Objective: We analyzed hotspot PIK3CA gene mutations in a series of esophageal squamous cell carcinomas associated or not with chagasic megaesophagus, as well as, in chagasic megaesophagus biopsies. We also checked for correlations between the presence of PIK3CA mutations with patients' clinical and pathological features. Methods: The study included three different groups of patients: i) 23 patients with chagasic megaesophagus associated with esophageal squamous cell carcinoma (CM/ESCC); ii) 38 patients with esophageal squamous cell carcinoma not associated with chagasic megaesophagus (ESCC); and iii) 28 patients with chagasic megaesophagus without esophageal squamous cell carcinoma (CM). PIK3CA hotspot mutations in exons 9 and 20 were evaluated by PCR followed by direct sequencing technique. Results: PIK3CA mutations were identified in 21.7% (5 out of 23) of CM/ESCC cases, in 10.5% (4 out of 38) of ESCC and in only 3.6% (1 case out of 28) of CM cases. In the CM/ESCC group, PIK3CA mutations were significantly associated with lower survival (mean 5 months), when compared to wild-type patients (mean 2.0 years). No other significant associations were observed between PIK3CA mutations and patients' clinical features or TP53 mutation profile. Conclusion: This is the first report on the presence of PIK3CA mutations in esophageal cancer associated with chagasic megaesophagus. The detection of PIK3CA mutations in benign chagasic megaesophagus lesions suggests their putative role in esophageal squamous cell carcinoma development and opens new opportunities for targeted-therapies for these diseases.
Keywords: Achalasia; Chagasic megaesophagus; Esophageal cancer; Esophageal squamous cell carcinoma; Mutation; PIK3CA; Trypanosoma cruzi